Design of a ball burnishing tool with interchangeable tip (2018)
The following work was carried out with the goal of studying the functionality of a previously realized design of an interchangeable indenter tool for the ball burnishing process in a numerical control milling machine with several AISI 1045 specimens, to identify and corroborate changes in the final roughness obtained and the averages of the same material with the application of the process, in addition to finding improvements in the process times, to reduce the dead times that translate into lower costs, and an improvement in the surface finish.